(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The study aimed to reveal the reality of the quality of the job life of the workers under study, and to determine the availability of wages, job stability, and the balance between personal life and work for the workers under study. The study relied on the deductive approach as a general approach to thinking, and on the descriptive-analytical approach, which is based on an accurate description of the phenomenon and its analysis to answer the objectives of the study and discuss its hypotheses. In collecting data, the researcher relied on a questionnaire. The study reached a set of results, including: the lack of an indicator of wages appropriate to the quality of working life among workers at Tishreen University, and this is evident through the answers of the sample members, where the average answers of the sample members on the wage axis decreased from the average neutrality (3), and the essential difference between The average wage axis and the average scale used (1.3567) and on the negative side of the scale, and the lack of an indicator of job stability for the quality of career life among workers at Tishreen University, and this is evident through the answers of the sample members, where the average answers of the sample members on the axis of job stability decreased from the average neutrality ( 3), and the essential difference between the average axis of job stability and the average of the scale used was (1,0191) and in the negative side of the scale.